PENGARUH PANDEMIC COVID-19 TERHADAP KOMPENSASI, KOMITMEN ORGANISASIONAL, KEPUASAN KERJA DAN KINERJA DOSEN (Studi Pada Dosen Yayasan Pendidikan Fajar Di Kota Makassar Provinsi Sulawesi Selatan) - A.NUR INSAN (Movere Journal, 2022)
The purpose of this study was to analyze the effect of covid-19 on compensation. The effect of covid-19 on organizational commitment. The effect of covid-19 on job satisfaction. The influence of covid-19 on lecturer performance. The effect of compensation on organizational commitment. The effect of compensation on job satisfaction. The effect of compensation on lecturer performance. The effect of organizational commitment on job satisfaction. This research is explanatory research with survey method. This research was conducted at Fajar University and Nitro Finance College in Makassar City, South Sulawesi Province. The research sample is 112 lecturers. Proportionate stratified random sampling was taken because the sample was stratified by using a questionnaire. Partial lies square (PLS) data analysis. The results of the study found that five hypotheses had a significant effect and three hypotheses had no significant effect, namely Covid-19 on job satisfaction. Compensation for job satisfaction. Compensation for lecturer performance.